Carcerality and Education: Toward a Relational Theory of Risk in Educational Institutions. (September 2022) - Dizon, Jude Paul Matias; Enoch-Stevens, Taylor; Huerta, Adrian H.
In this paper, we explore the logics underlying the policies and practices within K-12 schools, colleges, and universities that expose students to carceral systems, such as the police and prisons. Educational institutions at all levels have had the latitude to develop the capacity to discipline, surveil, and control students, which reproduce carceral logics within as well as create pathways to carceral systems. However, our scholarly understanding of such phenomena is bifurcated and uneven. While there is an extensive line of research on exclusionary discipline in the K-12 sector, similar scholarship is emergent at the postsecondary level. The goals of this paper are twofold. First, we review the ways in which carcerality informs the development of discipline, punishment, and control structures throughout the K-16 pipeline. Second, we introduce a relational theory of risk as a unified conceptual approach to examine carceral policies and practices in both the K-12 and the higher education sectors. From a relational risk perspective, we argue that carceral practices can be understood as a relationship between educational institutions and students who are perceived to be threats to institutional interests. Engaging with the organizational imperatives that lead to carceral practices, researchers and practitioners can better attend to dismantling racial exclusion in education.